PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 106163 BANDAR KLIPPA - Situmorang, Eciana P.A; Ananda, Lala Jelita; Rozi, Fahrur; Sirait, Albert Pauli; Sembiring, Masta Marselina (Universitas Negeri Medan, 2025)
This study aims to determine the influence of the Project Based Learning Model (PjBL) on the learning outcomes of social studies students in grade V of SDN 106163 Bandar Klippa. The method used in this study is a pseudo-experiment (Quasi Experiment). This study used two sample groups, namely the experimental group with 21 students and the control group with 21 students. The experimental group in this study was a class of students who received learning with the Project Based Learning (PjBL) model, while the control group was a group that used a conventional learning model. The instrument used in this study is in the form of a multiple-choice test that will be tested in a class with Nonequivalent Control Group Design. This can be seen through the acquisition of the average Post-Test score of students in the experimental class is 80.71 with a percentage of 85.71%. Meanwhile, the average Post-Test score of control class students was 71.90 with a percentage of 42.86%. Based on the results of the hypothesis test, a significant value of 0.003 was obtained. In accordance with the hypothesis testing criteria, if sig. (2-tailed) < 0.05 until Ha is accepted and Ho is rejected. Thus, it can be concluded that the use of the Project Based Learning (PjBL) learning model has an effect on the learning outcomes of social studies of grade V students of SDN 106163 Bandar Klippa, especially in the material Indonesiaku Kaya Hayatinya